Realising The Importance Of Your Immune System - Ahmad Mahfuz, Gazali (CodeBlue, 2021)
The First World Immunology Day was held on April 29, 2005 by the European Federation of Immunological Societies. Since then, World Immunology Day has been officially adopted by the International Union of Immunological Societies (IUIS). Since 2007, World Immunology Day has been commemorated by immunological societies around the world. Immunology is not a new held in medicine. Thucydides, a Greek historian and general from 5 BC, noted the importance of immunity during the plague of Athens in 430 BC, as documented in his book, The History of the Peloponnesian War.